Characteristics of Isolated Ventricular Septal Defects Less Likely to Close In Utero. (2nd February 2018) - Chau, Ann C.; Jones, Andrew; Sutherland, Monique; Lilje, Christian; Sernich, Stefan; Hagan, Joseph; Miller, Joseph
Abstract : Objectives: To determine the characteristics of fetal ventricular septal defects (VSDs) that will be less likely to close prenatally. Methods: In this 4‐year retrospective cohort study, 148 fetuses had a diagnosis of a VSD during a comprehensive fetal anatomy survey. The VSD diagnosis was confirmed by color and pulsed wave Doppler studies. These fetuses were followed monthly until their birth. They had postnatal echocardiography performed within 1 month of age to assess the persistence of a VSD. Fisher exact, Wilcoxon rank sum, and log rank tests and bivariate and multivariate logistic regressions were used to examine the association of each individual variable with prenatal VSD closure. Results: One hundred twenty‐five of 148 fetuses (84%) had prenatal VSD closure at a mean gestational age ± SD of 26.9 ± 4.5 weeks. Fetuses with a persistent VSD more frequently had other cardiac defects than the closed VSD group (12 of 23 versus 5 of 125; P < .001). Fetuses having a persistent VSD more frequently had an abnormal karyotype (9 of 23 versus 5 of 125; P < .001). The persistent VSDs were larger in their initial size (5.9 ± 8.4 mm versus 2.7 ± 0.8 mm; P = .002) and in their maximal prenatal size (6.0 ± 9.1 mm versus 2.9 ± 0.9 mm; P < .001). The presence of associated cardiac defects (adjusted odds ratio = 0.071; P = .031) and an abnormal karyotype (adjusted odds ratio = 0.058; P = .021) were significantly associated with a lower likelihood of prenatal VSD closure. All VSDs with a maximal size of 2 mm or less closed prenatally. Conclusions: Fetuses with a complex cardiac defect or an abnormal karyotype were less likely to have prenatal VSD closure.